التأويل التداولي للحذف في شرح الاستراباذي على كافية ابن الحاجب: الكفاءات التأويلية وبناء المعنى - كحله, هجيرة (جامعة الوادي - University of Eloued, 2021)
يتمحور موضوع هذا العمل حول التأويل التداولي بما هو تطبيق لكفاءات المؤول الثلاث (اللسانية، التداولية، الاستدلالية)، والذي له عتبات يقف عندها (التعاقد، السياق، القصد)، وله مبادئ ينبني عليها (مبدأ التعاون، مبدأ الملاءمة، مبدأ التصديق ....)، يوجه فيه المؤول بموجب قواعد تراعي تلك المبادئ، وتمكنه من أن ينتقل من مرتبة المرسل إليه إلى مرتبة المؤول. هذا المنهج الجديد الذي خرجت به تداوليات التأويل على الساحة العلمية المعاصرة كأحدث ما وصلت إليه التأويلية الغربية في نسختها التداولية، سعت الباحثة إلى اختباره على مدونة "شرح الرضيّ الاستراباذي على كافية ابن الحاجب" في ظاهرة من ظواهرها المدروسة هي "الحذف"، إثباتا لأصالة الممارسة التراثية بعامة بما يجعلها نواة حقيقية للتنظيرات المعاصرة، وتَمثّل كل ذلك بخاصة عند الرضيّ لما أثبتته كفاءاته التأويلية من ملاءمة مع تلك الأنظار. وسعيا لبلوغ هذا الهدف، تألف هذا العمل من: مقدمة، وفصل تمهيدي، وثلاثة فصول تطبيقية، وخاتمة. الفصل التمهيدي: هو مهاد نظري يتضمن التعريف بالمصطلحات المفاتيح: التأويل، الحذف من المنظورين العربي، والغربي، مصطلح الكفاءة وما يتعلق بها من علوم، التعريف ببناء المعنى في اللغة والاصطلاح، ثم التعريف بالاستراباذي وشرحه للكافية. الفصل الأول: يهتم بإثبات الكفاءات التأويلية للرضي (اللسانية، التداولية، الاستدلالية) في باب "حذف الأسماء"، وكيفية بنائه للمعنى فيه . الفصل الثاني: يسعى إلى إثبات كفاءات الرضيّ المذكورة في باب "حذف الفعل والجملة" ورصد كيفية بنائه للمعنى. الفصل الثالث: يروم إثبات كفاءات الرضيّ المذكورة في باب "حذف الحروف" وتبيّن كيفية بنائه للمعنى. الخاتمة: هي حوصلة للنتائج المتوصل إليها، والتي أثبتت انتماء تأويلات الرضيّ إلى التأويل التداولي كما تصفه تداوليات التأويل، وانبناء المعاني عنده على تفاعل التدليل والتأويل مع الاستعانة بآليات أخرى بانية للمعنى من قبيل: التفات المعنى، الحجاج، القراءات، الأساس التقابلي The subject of this study is centered around the pragmatic interpretation in the application of the three interpreter competencies (linguistic, pragmatic, inferential), and it has principles by which it is founded upon (the principle of cooperation, the principle of adequacy, the principle of believability …), the interpreter is guided by a set of rules respecting those principles mentioned above , and it enables the interpreter to elevate from a the level of a receiver to the level of the interpreter. This new approach that come out of the field of pragmatic interpretation as the latest invention of western interpretation in its pragmatic version, the researcher wanted to put that to the test on the book "Sharh al-Radhi al-Istrabadi ala kafiyyat Ibn al-Hajeb" in one of its studied phenomenon which is "the ellipses" , proving the authenticity of the heritage practice on general which makes it a true kernel for contemporary theories, all of this was very present especially in the case of "Al-Radhi" which his interpreter competencies proves a high level of adequacy with the new perspectives. To reach this objective, this work is made up of: an introduction, Introductory chapter, three application chapters and a conclusion. The Introductory chapter: a theoretical introduction including the definitions of all the keywords: interpretation, ellipses from an Arabic and western perspectives, the term of competency and all the fields connected to it, defining the construction of meaning in both Language and convention, then introducing al-Istrabadi and his "Sharh al-Kafiyyat". The first chapter: is dedicated to proving al-Radhi's interpretive competencies (linguistic, pragmatic, inferential) in the chapter of "Hadhaf el-Asmaa", and the way he constructed the meaning in that chapter. The second chapter: seeks to prove al-Radhi's interpretive competencies mentioned in the chapter " hadhaf alfiel w aljumla" and the process of constructing it's meaning. The third chapter: seeks to prove al-Radhi's interpretive competencies mentioned in the chapter " hadhaf alhuruf" and the process of constructing it's meaning. The conclusion: it is a summary of all the findings reached, which proved the adequacy of al-Radhi's interpretations with the pragmatic interpretation as described by the pragmatics of interpretation, and the construction of meaning according to him based on the interaction between approbation and interpretation with applying other instruments that constructs meaning as: the turning of meaning, argumentation, readings, Contrastive basis
أطروحة دكتوراه في الأدب العربي تخصص: لسانيات عربية
Keywords: التأويل التداولي، كفاءات المأول، الحذف، شرح الرضي الاستراباذي، بناء المعنى; Pragmatic interpretation , Interpreter competencies , The ellipses , Sharh al-Radhi al-Istrabadi , Construction of meaning